Fire's impact on threat detection and risk perception among vervet monkeys: Implications for hominin evolution. Issue 145 (August 2020) - Herzog, Nicole M.; Parker, Christopher; Keefe, Earl; Hawkes, Kristen
Abstract: The spatial behavior of primates is shaped by many factors including predation risk, the distribution of food sources, and access to water. In fire-prone settings, burning is a catalyst of change, altering the distribution of both plants and animals. Recent research has shown that primates alter their behavior in response to this change. Here, we study primates' perceived threat of predation in fire-modified landscapes. We focus on the predator-related behaviors of vervet monkeys ( Chlorocebus pygerythrus ) after controlled burning events. We compare the occurrence of vigilance and predator-deterrent behaviors, including alarm calls, scanning, and flight across different habitats and burn conditions to test the hypothesis that subjects exhibit fewer predator-specific vigilance and predator-deterrent behaviors in burned areas. The results demonstrate that predator-related behaviors occur less often in burned habitats, suggesting that predators are less common in these areas. These results provide foundations for examining hypotheses about the use of fire-altered landscapes among extinct hominins. We set these data in the context of increasing aridity, changes in burning regimes, and the emergence of pyrophilia in the human lineage.